2010
DOI: 10.14227/dt170310p20
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Dissolution Kinetics of Amlodipine Tablets Marketed in Russia Under Biowaiver Conditions

Abstract: The current paper is devoted to in vitro dissolution kinetics studies of amlodipine tablets marketed in Russia under biowaiver conditions. Dissolution kinetics studies were carried out according to WHO Guidance. Dissolution profiles of test and reference (innovator) amlodipine tablets were considered equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…However, the greatest IDR values were obtained when 0.1 M HCl was used as a dissolution medium, even causing the compressed material to loosen, regardless of the compaction pressure used (as observed in assays E3, E6 and E9). This behavior is due to the basic property of amlodipine besylate (pKa=8.7), indicating that it is much more soluble in an acidic medium (Shoin et al, 2010;van Zwieten, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…However, the greatest IDR values were obtained when 0.1 M HCl was used as a dissolution medium, even causing the compressed material to loosen, regardless of the compaction pressure used (as observed in assays E3, E6 and E9). This behavior is due to the basic property of amlodipine besylate (pKa=8.7), indicating that it is much more soluble in an acidic medium (Shoin et al, 2010;van Zwieten, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to amlodipine, different studies have been performed to determine the release of amlodipine Besylate tablets using various dissolution conditions, and results are discordant. Thus, Shohin et al [13] evaluated the dissolution characteristics of the reference product and one product marketed in Russia, using 500 mL of USP buffer solutions at pH 1.2, 4.5 and 6.8 and apparatus 2 at 75 rpm. They found that the products dissolved very rapidly at pH 1.2 and 4.5, while at pH 6.8 they behaved as rapidly dissolving products and dissolution profiles were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to its permeability, Caron et al [12] found that neutral amlodipine shows high permeability while cationic amlodipine does not permeate. In vivo studies have shown that although bioavailability is low (60 -65 %), its permeability could be considered high due to metabolite excretion in urine (90 -95 %) [13]. Moreover, the WHO guidance assigned amlodipine to BCS class 1 [4]; therefore, it has been considered as a candidate for a biowaiver through dissolution testing.…”
Section: Introductionmentioning
confidence: 99%
“…Both evaluated drugs were "rapidly dissolving" [ Table 1] because the active pharmaceutical ingredient release at time point 30 min was >85%. [21][22][23][24][25] Table 1.…”
Section: If Both the Test And The Reference Dosage Forms Are Verymentioning
confidence: 99%